2006
DOI: 10.1002/adem.200600164
|View full text |Cite
|
Sign up to set email alerts
|

Negative Strain‐rate Sensitivity in a Nanostructured Aluminum Alloy

Abstract: Since grain boundaries and triple junctions occupy a considerable volume fraction in nanostructured materials, grainboundary mediated deformation mechanisms, for instance, Coble diffusion creep or grain boundary sliding, are expected to play a significant role in the deformation of nanostructured materials, even at room temperature. The grain-boundary mediated deformation mechanisms, may lead to a large value of strain rate sensitivity in nanostructured materials. Recently, the strain rate sensitivity of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…The QS results show a maximum flow stress at low strains followed by nearly perfectly plastic behavior, and perhaps even weak strain softening. Similar behavior has been observed for a similar cryomilled Al-5083 material [33]. This behavior is perhaps associated with deformation instabilities arising from dynamic strain aging effects [33,34].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The QS results show a maximum flow stress at low strains followed by nearly perfectly plastic behavior, and perhaps even weak strain softening. Similar behavior has been observed for a similar cryomilled Al-5083 material [33]. This behavior is perhaps associated with deformation instabilities arising from dynamic strain aging effects [33,34].…”
Section: Resultssupporting
confidence: 79%
“…Similar behavior has been observed for a similar cryomilled Al-5083 material [33]. This behavior is perhaps associated with deformation instabilities arising from dynamic strain aging effects [33,34]. In summary, the CS tests suggest that microstructure evolution is limited in this cryomilled material at these temperatures.…”
Section: Resultssupporting
confidence: 76%
“…There are several reports showing negative strain rate sensitivities in nanostructured metals of Ti after ECAP followed by cold rolling [55] and Al alloys produced through cryomilling [56,57]. The consistent behavior of these metals involves a strain-rate dependent instability of plasticity attributed to the occurrence of dynamic strain aging (DSA) leading to the local formation of solute clusters on forest dislocations resulting in a strengthening of dislocation junctions [58].…”
Section: The Improvement In Micro-mechanical Response By Pdamentioning
confidence: 99%
“…[41] Further investigation of a cryomilled Al-5083 alloy demonstrated that the negative strain rate sensitivities in both nanostructured and coarsegrained Al alloys were caused by DSA. [42] Specifically, DSA occurs due to the formation of solute clusters on forest dislocations resulting in a strengthening of dislocation junctions where the presence of a cluster on a forest dislocation modifies the strength of the junction formed by the interaction of dislocations with mobile unclustered dislocations. Thus, faster deformation allows for less clustering by diffusion of solute atoms to the mobile dislocations and this produces junctions having lower strength.…”
Section: Micro-mechanical Behavior Of the Al-mg Nanocompositementioning
confidence: 99%
“…Thus, faster deformation allows for less clustering by diffusion of solute atoms to the mobile dislocations and this produces junctions having lower strength. [39,42] It should be noted that the PLC effect is generally observed over a limited range of temperature and strain rate and thus the testing conditions of room temperature to 50 C and strain rates of <10 À1 s À1 were suggested for commercial Al alloys demonstrating a negative strain rate sensitivity. [36] An earlier experiment on a discontinuously reinforced metal matrix composite of a powder-consolidated aluminum 6092/B 4 C demonstrated a negative strain rate sensitivity at strain rates <1.0 s À1 .…”
Section: Micro-mechanical Behavior Of the Al-mg Nanocompositementioning
confidence: 99%